Fra-2/AP-1 controls adipocyte differentiation and survival by regulating PPAR? and hypoxia - Luther, Julia; Ubieta Hernández, Kenia; Hannemann, Nicole; Jimenez, Maria; Garcia-Cuellar, Maria-Paz; Zech, C.; Schett, Georg; Wagner, E. F.; Bozec, Aline (Cell Death and Differentiation, 2014)
Adipocyte cell number is a crucial factor for controlling of body weight and metabolic function. The regulation of adipocyte numbers in the adult organism is not fully understood but is considered to depend on the homeostasis of cell differentiation and apoptosis. Herein, we show that targeted deletion of the activator protein (AP-1)-related transcription factor Fra-2 in adipocytes in vivo (Fra-2(?adip) mice) induces a high-turnover phenotype with increased differentiation and apoptosis of adipocytes, leading to a decrease in body weight and fat pad mass. Importantly, adipocyte cell numbers were significantly reduced in Fra-2(?adip) mice. At the molecular level, Fra-2 directly binds to the PPAR?2 promoter and represses PPAR?2 expression. Deletion of Fra-2 leads to increased PPAR?2 expression and adipocyte differentiation as well as increased adipocyte apoptosis through upregulation of hypoxia-inducible factors (HIFs). These findings suggest that Fra-2 is an important checkpoint to control adipocyte turnover. Therefore, inhibition of Fra-2 may emerge as a useful strategy to increase adipocyte turnover and to reduce adipocyte numbers and fat mass in the body.
EVALuna2:12913

Tumor Infiltration with CD20+CD73+ B Cells Correlates with Better Outcome in Colorectal Cancer - Hansen, Frederik; Wu, Zhiyuan; David, Paul; Mittelstädt, Anke; Jacobsen, Anne; Podolska, Malgorzata; Ubieta Hernández, Kenia; Brunner, Maximilian; Kouhestani, Dina; Swierzy, Izabela; Roßdeutsch, Lotta; Klösch, Bettina; et al. (International Journal of Molecular Sciences, 2022)
Immunotherapy has become increasingly important in the treatment of colorectal cancer (CRC). Currently, CD73, also known as ecto-5′-nucleotidase (NT5E), has gained considerable interest as a potential therapeutic target. CD73 is one of the key enzymes catalyzing the conversion of extracellular ATP into adenosine, which in turn exerts potent immune suppressive effects. However, the role of CD73 expression on various cell types within the CRC tumor microenvironment remains unresolved. The expression of CD73 on various cell types has been described recently, but the role of CD73 on B-cells in CRC remains unclear. Therefore, we analyzed CD73 on B-cells, especially on tumor-infiltrating B-cells, in paired tumor and adjacent normal tissue samples from 62 eligible CRC patients. The highest expression of CD73 on tumor-infiltrating B-cells was identified on classswitched memory B-cells, followed by naive B-cells, whereas no CD73 expression was observed on plasmablasts. Clinicopathological correlation analysis revealed that higher CD73+ B-cells infiltration in the CRC tumors was associated with better overall survival. Moreover, metastasized patients showed a significantly decreased number of tumor-infiltrating CD73+ B-cells. Finally, neoadjuvant therapy correlated with reduced CD73+ B-cell numbers and CD73 expression on B-cells in the CRC tumors. As promising new immune therapies are being developed, the role of CD73+ B-cells and their subsets in the development of colorectal cancer should be further explored to find new therapeutic options.
CRIS-Team Scopus Importer:2022-05-20
Keywords: B-cells; CD20; CD73; colorectal cancer; neoadjuvant treatment